Vitamin D and MAFLD: a bibliometric and visual analysis from 2007 to 2024 - Zhang, Jiaguo; Wu, Sipeng; Huang, Junqian; Sun, Xuehua; Chen, Jianjie; Shang, Binyi (Frontiers in Nutrition, 2025)
BackgroundVitamin D plays a critical role in the mechanism of metabolic fatty liver disease. Emerging evidence suggests its potential as both a diagnostic biomarker and therapeutic target. Despite growing research interest, systematic analyses of this field remain limited.PurposeThis study conducts a bibliometric and visual analysis of literature on the link between vitamin D and metabolism-related fatty liver disease, mapping the research landscape, trends, hotspots, and frontiers to inform future investigations.MethodsThe Web of Science Core Collection (WoSCC) database was comprehensively explored for literature pertaining to metabolism-related fatty liver disease and vitamin D from 2007 to 2024. Using CiteSpace (v6.1. R6) and VOSviewer (v1.6.20) software, we evaluated publication trends, regional and national contributions, institutional outputs, journal allocation, author collaborations, reference citations, and keyword patterns.ResultsA total of 480 publications were analyzed, demonstrating a consistent annual increase. China, the United States, and Italy emerged as leading contributors, with Shanghai Jiao Tong University, Capital Medical University, and Sichuan University being the most productive institutions. The most cited and prolific author was Ilaria Barchetta. Hepatology ranked as the journal with the highest volume of publications in this field. The top most frequently used keywords are “vitamin D,” “NAFLD,” and “insulin resistance.” Burst detection indicated “T2DM” and “acid” as emerging research foci.ConclusionThis study provides insights into current trends and prospects in research on vitamin D and metabolism-associated fatty liver disease, focusing on insulin resistance, obesity, osteoporosis, and ACID. While the efficacy of vitamin D supplementation remains uncertain, the findings offer guidance for broader future studies.